PENGEMBANGAN PENILAIAN PENDIDIKAN AGAMA ISLAM PADA JENJANG MI - Rima Dewi Setiani I; Ulfa (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This study aims to describe the development of Islamic Religious Education (IRE) assessment in Madrasah Ibtidaiyah as an effort to nurture students who are faithful, pious, and have noble character. IRE is understood as education that emphasizes a balance between cognitive, affective, and psychomotor aspects in accordance with Islamic guidance and the Merdeka Curriculum. This study uses a qualitative method through a literature study with primary and secondary sources from books, journals, and relevant research results. This study is expected to provide an understanding of the concept of authentic assessment that is comprehensive, sustainable, and in line with the values of the Pancasila Student Profile and Rahmatan lil 'Alamin. The results of the study indicate that PAI assessment must be designed systematically, fairly, and accountably to measure and nurture religious character. In conclusion, the development of PAI assessment in MI is an important step in improving the quality of Islamic education and shaping students who excel spiritually, morally, and academically.